Facile Sonochemical Synthesis of Nanostructured Fewo4-Rgo and Cuco2o4 Nanocomposite for High-Rate Capability and Stable Asymmetric (Cuco2o4//Fewo4-Rgo) Supercapacitors - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier Ltd, 2023)
The present work reports iron tungstate (FeWO4) nanostructures with reduced graphene oxide (rGO) as a novel anode material for enhancing the electrochemical properties of asymmetric supercapacitors. The FeWO4-rGO composite nanostructures were successfully synthesized by the one-pot sonochemical method. The synthesized nanocomposites crystal structure and phase purity were investigated using the powder X-ray diffraction (XRD) technique. The Fourier transform infrared (FT-IR) spectrograms demonstrate the presence of functional groups in the composite. The composite s morphology was examined using the high-resolution transmission electron microscopy (HR-TEM) and the field emission scanning electron microscopy (FE-SEM), and it was observed that the FeWO4 nanostructures were uniformly distributed on the reduced graphene oxide surface. The cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) analyses were used to evaluate the electrochemical performance. After 5000 cycles at 10 mA cm− 2, the FeWO4-rGO composite achieved a better rate of efficiency and outstanding cycling performance, with capacitance retained at 68% and 77.8%, respectively. In 1 M Na2SO4, an asymmetric device (CuCo2O4//FeWO4-rGO composite) achieved a high energy density of 21.5 W.h Kg−1 and a power density of 147 W Kg−1. In the FeWO4-rGO nanocomposite, the reduced graphene oxide could enhance the conductivity and the free diffusion processes for the quick ion transport and easy ion access to the storage sites. The obtained results indicated that the FeWO4-rGO nanocomposite could be a good anode electrode material for the next-generation energy storage applications. © 2023 Elsevier B.V.